Sleisenger &Fordtran's Gastroinstestinal and Liver Disease: Pathophysiology/ Diagnosis/ Management - Marvin H. Sleisenger; Mark Feldman (Philadelphia : Saunders Elsevier, 2006)
Provide evidence-based perspectives on all clinically relevant topics, explaining step by step how to apply the latest advances in practice. Succinct yet comprehensive discussions provide just the right amount of clinical detail. Plus, a consistent organization and full-color art program enable you to quickly and easily access needed information. Offers more than 1,000 illustrations, photographs, and tables (400 in full color) that promote a visual grasp of the material. Presents coverage of the hottest topics in today's practice, including GERD, non-alcoholic fatty liver disease, ulcerative colitis, and Barretts esophagus, as well as the psychosocial aspects of gastrointestinal and liver diseases. Features four new chapters covering complimentary and alternative medicine palliative care gastrointestinal stromal tumor (GIST) and eosinophilic disorders, plus expanded information on obesity and nutrition
Keywords: Diseases of the Digestive System; Foie Maladies